Effect of Organic Manures on the Yield and Quality of True Seeds of Onion - Mollah, M. R. A.; Ali, M. A.; Ahmad, M.; Hassan, M. K.; Prodhan, M. Z. H. (International Journal of Applied Sciences and Biotechnology, 2015)
The present study was stimulated by the problem of onion seed production where seed production is possibly only winter period after which rapid increase in temperature as well as early shower adversely affect the quality of seed. The experiment was laid out in a randomized complete block design with four replications to determine optimum doses of manures and fertilizers for maximizing quality true seeds of onion. Six treatments viz. T1= Only inorganic fertilizer recommended by Spices Research Centre (SRC), T2 = T1 + Cowdung manure 7.5 t/ha, T3= T1 + Poultry manure 5 t/ha, T4= T1 + Mustard oil cake 5 t/ha, T5= T1 + Dhaincha 5 t/ha and T6= Control (No manures and fertilizer application)were consisted to achieve the objective. The research work was done at On-Farm Research Division, BARI, Bogra during September, 2010 to June, 2011. The results revealed that the growth parameters, seed yield components, health and quality of harvested seeds were significantly influenced by the different treatments. Results showed that among different treatments, inorganic fertilizer Urea, TSP, MoP, Gypsum, Zinc oxide and Boric acid @ 250, 275, 150, 110, 3 and 5 kg/ha, respectively along with Cowdung 7.5 t/ha was the best for true seed production of onion at Bogra region in Bangladesh.Int J Appl Sci Biotechnol, Vol 3(2): 162-166 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12279